One‐Step Synthesis of Hierarchical Structure Polydimethylsiloxane Films with Micro‐/Nanosurfaces for Application in Triboelectric Nanogenerators. Issue 12 (13th October 2021) - Wang, Jiaxin; Wang, Kun; Qiu, Zhirong; Liu, Ye; Chen, Rong; Wu, Chaoxing; Lin, Jintang
Abstract : Surface optimization of tribomaterial is an effective approach for enhancing the output performance of triboelectric nanogenerators (TENGs). Developing advanced surface structures and their mass fabrication method is the essential technology component of TENG‐based electronics. Herein, a facile, scalable synthesis of hierarchical structure polydimethylsiloxane (HS‐PDMS) films with micro‐/nanosurface morphology and their application in TENGS are demonstrated. The micromorphology of the PDMS surface with random microcraters is achieved using water droplet‐based microtemplates and their rapid evaporation approach. Simultaneously, the nanomorphology on the microcrater surface with nanoripples is automatically formed under the action of surface tension of the PDMS film. The effect of water droplet mass fraction and the rate of heating, which play key roles in the surface morphology and the device's electrical output control, are investigated. This fabrication method of HS‐PDMS is simple and scalable, providing a promising solution of developing tribomaterial for practical TENG‐based electronic devices. Abstract : A facile, scalable synthesis of hierarchical structure polydimethylsiloxane (PDMS) films with micro‐/nanomorphology is demonstrated for enhancing the triboelectric nanogenerator performance. The micromorphology of the surface is fabricated using water droplet‐based microtemplates. The microcraters are formed during the rapid evaporation of water droplets. The nanoripples are automatically formed under the action of surface tension of the PDMS film.